МЕТОДИЧЕСКАЯ СИСТЕМА ФОРМИРОВАНИЯ КОМПЕТЕНТНОСТИ ПОНИМАНИЯ ПРОЧИТАННОГО У БУДУЩИХ СТУДЕНТОВ-ЭКОНОМИСТОВ ПОСРЕДСТВОМ ПРОБЛЕМНОГО ЧТЕНИЯ - Зухра НАРБЕКОВА (International Scientific and Current Research Conferences, 2023)
In this article, the author shows that reading skills not only help students develop critical thinking and analytical skills, but also prepares them for future professional activities where these skills will be needed. At the same time, this direction requires further research and development to ensure maximum effectiveness and applicability in various educational contexts.